Impact of low-dose municipal sewage sludge compost treatments on the nutrient and the heavy metal contents in a chernozem topsoil near Újkígyós, Hungary - Ladányi Zsuzsanna; Csányi Katalin; Perei Katalin; Farsang Andrea; Bodor Attila; Kézér Adrienn; Barta Károly; Babcsányi Izabella (2020)
Agriculture is one of the major fields, where sewage sludge can be used. Its high nutrient content can contribute to the improvement of important soil properties, such as nutrient content, water balance and soil structure. However, sewage sludge may contain hazardous components, such as pathogens and pollutants. Therefore, it is important to monitor the effects of its field application. In this paper, we assessed the impacts of two low-dose (2.5 m3 /ha) municipal sewage sludge compost applications (in 2013 and in 2017) in a 5.6 ha arable land in southeast Hungary (near Újkígyós), located in the Hungarian Great Plain. The nutrient and the heavy metal contents in the upper soil layer (0-30 cm) of the studied Chernozem soils were compared between two sampling campaigns in 2013 (before the compost applications) and in 2018 (after the compost applications). Basic soil properties (pH, salinity, humus content, carbonate content, Arany yarn number) complemented with nutrient content (K2O, P2O5, NO2+ NO3) and heavy metal content (Cd, Co, Cr, Cu, Ni, Pb and Zn) analyses were performed. The results show that no significant change can be noticed in the baseline parameters over the 5-year period. The slight increase in the P2O5, NO2+ NO3 content is closely related to the beneficial effects of the sewage sludge deposition. The soil-bound heavy metal load did not increase significantly as a result of the compost treatments, only nickel showed a slight increase in the topsoil. In all cases the heavy metal concentrations did not reach the contamination thresholds set by Hungarian standards. The results provided positive evidences proving that low dose municipal sewage sludge compost disposal on agricultural land is safe, and can be considered as a sustainable soil amendment for agriculture in compliance with legal requirements.
Keywords: Természettudományok; Föld- és kapcsolódó környezettudományok